The Role of cf-HPV DNA as an Innovative Biomarker for Predicting the Recurrence or Persistence of Cervical Cancer - Márcia Poinho; Laura L. M. S. Dias; Layane S. Pinheiro; Flávia Níniver O. Gomes; Heidy H. M. F. Rondon; Mikele P. de Oliveira; Jhonnatan S. Souza; Higino F. Figueiredo; Daniel L. Lira; José E. Levi; Valquíria C. A. Martins; Kátia L. Torres (Viruses)
Background: Cervical cancer is highly prevalent among women in Amazonas, Brazil, mainly due to low screening coverage, and is diagnosed at a late stage, which compromises the treatment efficacy and survival rates. After treatment, recurrence is frequent, and there are few follow-up options to detect it. This highlights the urgent need for less-invasive biomarkers to monitor affected patients. Methods: This study employed real-time PCR, targeting the E7 gene of HPV types 16 and 18 to analyze cell-free DNA from plasma samples from 39 cervical cancer patients treated at the Oncology Control Center Foundation in Amazonas, Brazil. Results: cf-HPV 16 DNA was detected in 54% of the samples before treatment. The socioeconomic and behavioral data showed that 46.2% of the patients had low educational levels, 77% reported having a low income, 79.5% experienced an early sexual activity onset, and 15.4% had never undergone cytological screening. Persistence or recurrence occurred in 30.8% of cases over 4–33 months of follow-up, with cf-HPV DNA detectable in 75% of these cases. Conclusions: cf-HPV DNA in plasma is a promising biomarker for post-treatment surveillance, facilitating the earlier detection of persistence/recurrence. Incorporating this biomarker into clinical protocols could enhance outcomes and survival, particularly in underserved regions like the Amazon, where the access to healthcare is limited.